PERANAN SISTEM INFORMASI AKUNTANSI PADA BISNIS UKM - Hazzar Al Oktha Rahmatika; Hwihanus Hwihanus (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
Accounting information system is an information system that deals with everything related to accounting. Accounting itself is actually an information system. The role of accounting information systems for small and medium enterprises (SMEs) is almost the same as for large companies. Make economic decisions when conducting business, including decisions about market development, pricing, and preparing financial statements in accordance with accounting principles. To obtain reports or information that is accurate, timely and reliable, AIS in the digital era cannot be done without using a computer device. In computer automation, the use of manual labor will soon be abandoned.